Event-Triggered Consensus Control of Nonlinear Strict Feedback Multi-Agent Systems - Jiaojiao Zhuang; Zhenxing Li; Zongxiang Hou; Chengdong Yang (Mathematics, 2022)
In this paper, we investigate the event-triggered consensus problems of nonlinear strict feedback MASs under directed graph. Based on the high-gain control technique, we firstly give a state-based event-triggered consensus algorithm and prove that Zeno behavior can be excluded. When the full state information is unavailable, a high-gain observer is given to estimate state information of each agent and an observer-based algorithm is developed. Finally, we give an example to verify the effectiveness of both state-based and observer-based event-triggered consensus algorithms.